Modeling Ion propulsion plume interactions with spacecraft in formation flight - Kafafy, Raed; Yong, Cao (Royal Aeronautical Society, 2010)
This paper presents a simulation study of ion thruster plume effects on formation flying spacecraft. Two formation flight applications using micro-ion propulsion are considered: an L2-Halo orbit interferometer formation and a LEO micro-satellite formation. Worst case scenarios in both missions have been investigated. We focus our study on thruster configurations resulting in possible indirect plume impingement on satellites outside of the direct impingement zone. Indirect impingement which cannot be predicted except through plasma simulation or in-flight measurements might expose critical spacecraft elements such as optical sensors to a harsh contamination environment. A high-fidelity electrostatic plasma simulation code for parallel computing platforms was used in the study. In our study, we found that using miniature scale ion propulsion in both formation missions creates a very low charge-exchange plasma environment which results in tolerable contamination environment for other spacecraft in the formation.